2010
DOI: 10.1016/j.jembe.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

An improved technique for estimating short-term survival of released line-caught fish, and an application comparing barotrauma-relief methods in red emperor (Lutjanus sebae Cuvier 1816)

Abstract: Promotion of better procedures for releasing undersize fish, advocacy of catch-and-release angling, and changing minimum legal sizes are increasingly being used as tools for sustainable management of fish stocks. However without knowing the proportion of released fish that survive, the conservation value of any of these measures is uncertain. We developed a floating vertical enclosure to estimate short-term survival of released line-caught tropical and subtropical reef-associated species, and used it to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 25 publications
3
36
0
1
Order By: Relevance
“…Contrasting post-release survival rates in congeneric species was also reported by Brown et al (2010), who found that two Lutjanids, L. sebae and Lutjanus campechanus, had post-release survival rates of 98.4% and 77% (as reported by Rummer and Bennett, 2005), respectively. Brown et al (2010) offer no explanation as to the cause of the difference in mortality rates.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Contrasting post-release survival rates in congeneric species was also reported by Brown et al (2010), who found that two Lutjanids, L. sebae and Lutjanus campechanus, had post-release survival rates of 98.4% and 77% (as reported by Rummer and Bennett, 2005), respectively. Brown et al (2010) offer no explanation as to the cause of the difference in mortality rates.…”
Section: Discussionsupporting
confidence: 61%
“…These authors reported 49% survival for G. hebraicum caught at depths to 59 m, with survival as low as 14% for fish caught between 45 m and 59 m. However, these authors used much smaller, circular (75 cm diameter) cages compared to those used in the current study. Brown et al (2010) found that the post-release survival of red emperor (Lutjanus sebae) was 0% in small cages compared to 98.4% using the larger cages deployed in the current study. St.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations